Risk factors associated with hypertension in Bhutan: findings from the National Health Survey. Issue 6 (31st December 2020) - Dendup, Tashi; Tshering, Pandup; Dorji, Tandin
Abstract : Purpose: This study examined the risk factors associated with hypertension in Bhutan. Design/methodology/approach: The cross-sectional data of 30, 889 adults from the National Health Survey of Bhutan was used in this study. Multivariable regression accounting for the complex survey design was performed to identify the risk factors. The backward elimination approach was applied in the multivariable analysis. Findings: The prevalence of hypertension was 17%. Increasing age, being female, being previously married, higher wealth status, past alcohol use, having diabetes, loneliness, health service use and low vegetable intake was associated with increased hypertension risk, whereas, higher education level, being employed and residing in the eastern region was associated with reduced risk. Age, gender, education, wealth status, diabetes status, loneliness and health service use were common factors in all the regions. Marital status and vegetable intake were associated with hypertension in the western and central regions, and alcohol use in the eastern and central regions. Originality/value: Affecting around one-sixth of the population, hypertension is a significant public health problem in Bhutan. Interventions to improve health education and access, motivate healthy lifestyles, and reduce harmful alcohol use, and strategies to create health-promoting social and built environments are needed to curb the hypertension epidemic and its consequences.